Effect of corn extract percentage (Zea mays L.) and variation of nitrogen sources on the quality of nata de corn: Pengaruh konsentrasi ekstrak jagung (Zea mays L.) dan variasi sumber nitrogen terhadap kualitas nata de corn - Dita Cahya Priyanti; Yannie Asrie Widanti; Merkuria Karyantina (Fakultas Sains dan Teknologi Unisri, 2025)
Nata de corn is nata made from corn. Corn contains the element carbon which can fulfill the needs of Acetobacter xylinum in the formation of nata. This study used corn extract to replace coconut water and used natural nitrogen sources from mung bean sprout extract, soybean sprout extract and cowpea sprout extract. The aimed study to determine characteristics of nata which the thickest and highest fiber. This study used factorial RAL, with 2 factors, namely factor 1 was the percentage of corn extract (10%; 20% and 30%) and factor 2 was the variation of nitrogen sources (mung bean sprout extract, soybean sprout extract and cowpea sprout extract). The purpose of this study was to determine the physicochemical characteristics of Nata de corn and determine the best formulation for Nata de corn. The results of the best treatment formulation in the manufacture of Nata de corn were 30% corn seed extract formulation with 7.5 ml soybean sprout extract, 2.05% crude fiber chemical characteristic test, 0.15% total sugar and 0.97% water content. The resulting nata de corn has organoleptic characteristics of a yellowish-white color with a value of 1.95; less elastic with an elasticity value of 2.06 and slightly springy with a value of 2.72. The results of physical observations with a thickness of 0.72 cm, a weight of 599.8 grams and a volume of 4 ml of fermented residual liquid. Nata de corn has the potential to be a source of food fiber.